Comment: A Selective Overview of Nonparametric Methods in Financial Econometrics - PHILLIPS, Peter C. B. (Institutional Knowledge at Singapore Management University, 2005)
These comments concentrate on two issues arising from Fan’s overview. The first concerns the importance of finite sample estimation bias relative to the specification and discretization biases that are emphasized in Fan’s discussion. Past research and simulations given here both reveal that finite sample effects can be more important than the other two effects when judged from either statistical or economic viewpoints. Second, we draw attention to a very different nonparametric technique that is based on computing an empirical version of the quadratic variation process. This technique is not mentioned by Fan but has many advantages and has accordingly attracted much recent attention in financial econometrics and empirical applications.